Facilitation of learning in the context of the transformation of the traditional education system (Acta Education, 2024)
In this article, the author explores the main principles of traditional education and the facilitation of learning, as well as the main reasons for its effectiveness. The author also analyzes the personality of a learning facilitator and conducts a survey among students. This article is relevant for anyone dealing with the challenges of the modern educational system.